The lily theatre - Wang, Lulu (Nan A. Talese/Doubleday, 2000)
Wang tells the story of her adolescence during the Chinese Cultural Revolution, much of it spent with her mother in a re-education camp. There, her secret teachers were some of China's foremost thinkers who helped her distinguish truth from propaganda, and her refuge from reality was a pond, her Lily Theatre